Possibilities of Analyzing Sources of Impurities in Hydraulic Oil - Breznicka, Alena; Mikus, Pavol; Timarova, Ludmila; Kohutiar, Marcel; Krbata, Michal (Manufacturing Technology Journal, 2024)
The task of comprehensive machine care, monitoring of reliability and maintenance is currently a priority not to wait for a malfunction, but to prevent malfunctions before they occur. In the possibilities of mod-ern diagnostic tools, this activity is the task of oil analysis, which is a highly effective tool for monitoring the condition of hydraulic oils during their long-term operation. It is possible to prevent the failure of the entire system by regular monitoring of the technical condition of oils based on the analysis of hydraulic oil pollution. Oil analysis can reveal the amount of additive elements, oil pollution, the amount of addi-tives and changes in the physico-chemical parameters of the oil. In order to determine the current state of the oil filling, it is necessary to use a suitable diagnostic method. The submitted contribution de-scribes an experiment aimed at evaluating the state of hydraulic oil by means of EDX (Energy-dispersive X-ray spectroscopy) analysis, DSC (Different Scanning Calorimetry) analysis and infrared spectroscopy.
Keywords: EDX analysis; Reliability; Oil pollution; Additives; Infrared spectroscopy